A simulation analysis of an extension of one-dimensional speckle correlation method for detection of general in-plane translation - Hamarová, Ivana; Smíd, Petr; Horváth, Pavel; Hrabovský, Miroslav (TheScientificWorldJournal, 2014)
The purpose of the study is to show a proposal of an extension of a one-dimensional speckle correlation method, which is primarily intended for determination of one-dimensional object's translation, for detection of general in-plane object's translation. In that view, a numerical simulation of a displacement of the speckle field as a consequence of general in-plane object's translation is presented. The translation components a x and a y representing the projections of a vector a of the object's displacement onto both x- and y-axes in the object plane (x, y) are evaluated separately by means of the extended one-dimensional speckle correlation method. Moreover, one can perform a distinct optimization of the method by reduction of intensity values representing detected speckle patterns. The theoretical relations between the translation components a x and a y of the object and the displacement of the speckle pattern for selected geometrical arrangement are mentioned and used for the testifying of the proposed method's rightness.
Keywords: pohyb těles; Motion; teoretické modely; Models, Theoretical